Pelanggaran Kesantunan Berbahasa pada Acara Rakyat Bersuara: Orang Besar di Balik Gaduh Ijazah Jokowi: Violation of Language Politeness at the People's Voice Event: The Big Man Behind the Jokowi Diploma Uproar - Suci Sri Wahyuni; Andiopenta Purba; Deri Rachmad Pratama; Akhyaruddin Akhyaruddin (Universitas Tidar, 2025)
This study aims to describe the forms of language politeness violations found in the Rakyat Bersuara program entitled